Bleeding Complications in Patients Undergoing Intrathecal Drug Delivery System Implantation. Issue 12 (3rd March 2017) - Warner, Nafisseh S; Bendel, Markus A; Warner, Matthew A; Strand, Jacob J; Gazelka, Halena M; Hoelzer, Bryan C; Mauck, William D; Lamer, Tim J; Kor, Daryl J; Moeschler, Susan M
Abstract: Introduction: Intrathecal drug delivery systems (IDDSs) have dramatically improved analgesia and the functional status of cancer patients and those with chronic pain states. However, given the close proximity to the neuraxis and frequent concomitant use of antiplatelet or anticoagulant medications, this intervention is not without risk. The goal of this investigation was to determine the incidence of bleeding complications following IDDS placement. Methods: This is a retrospective review from 2005 through 2014 of adult patients undergoing IDDS implantation or revision at a tertiary care center. The primary outcome was a bleeding-related neurological complication requiring emergency medicine, neurology, or neurosurgical evaluation within 31 days. Results: A total of 247 procedures were performed on 216 unique patients. Patients received aspirin or nonsteroidal anti-inflammatory drugs (NSAIDs) within seven days of needle placement for 64 procedures (25.9%). A preprocedural platelet count or international normalized ratio (INR) was available within 30 days for 138 procedures (55.9%). Of these, two patients had a platelet count lower than 100 x 10 9 /L and one patient had an INR of 1.5 or higher at the time of the procedure. One neurological complication was identified (0.4%) that was not related to procedural bleeding. Similarly, three patients (1.2%) received a periprocedural red blood cell transfusion, none of which were related to procedural bleeding. Conclusion: No cases of bleeding-related neurological complications were identified following IDDS placement or revision, including in those receiving aspirin or NSAIDs. Future investigations with larger numbers are needed to further explore the safety of antithrombotic therapy continuation or discontinuation periprocedurally.